Impact of bacterial infections in seminal fluid on delayed male fertility: A comparative study between case and control groups - S. A. S. Al-Sultan; W. S. Eid; I. A. Abdulhameed; Y. H. Thanoon (Regulatory Mechanisms in Biosystems, 2025)
Bacterial persistence in seminal fluid, known as bacteriospermia, is increasingly recognized as a significant contrib u tor to male infertility. This study investigates the prevalence of bacteriospermia in subfertile men, assesses its impact on semen quality, and identifies the specific bacterial species involved. This case-control study involved 78 male participants, divided into two groups: 39 men experiencing delayed c onception (case group) and 39 men with proven fertility (control group). P articipants were chosen b ased on predetermined inclusion and exclusion criteria,. Comprehensive questionnaires and clinical assessments were used in the data gathering process. Semen samples were collected and measured for volume, pH, sperm concentration, motility, morphology, and viability following WHO guidelines. Bacterial identification was done using Gram staining, culture methods, and the Vitek 2 system. In the case group, 79.5% of patients had bacterial persistence, while in the control group it was seen in 35.9%. Isolated bacteria in the case group most commonly included Staphylococcus haemolyticus , 25.6%; Enterococcus faecalis , 12.8%; and Staphylococcus lentus , 10.3%. S ubstantial di f ferences were recorded between case and control groups for sperm motility, concentration, and morphology. Moreover, the case group had higher percentages for smokers, wearers of tight clothing, consum ers of alcohol , and those accustomed to prolonged sitting, which were found to be statistically significant risk factors. This study underscores the pivotal role of bacterial persistence in seminal fluid in the aetiology of male infertility. Addressing bacteriospermia by using better dia g nostic and therapeutic strategies can improve reproductive outcomes and clinical care for affected individuals.